2019
DOI: 10.3390/foods8050170
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effect of Extract from Nelumbo Nucifera L., Morus Alba L., and Raphanus Sativus Mixture in 3T3-L1 Adipocytes and C57BL/6J Obese Mice

Abstract: The antioxidant and anti-adipogenic activities of a mixture of Nelumbo nucifera L., Morus alba L., and Raphanus sativus were investigated and their anti-obesity activities were established in vitro and in vivo. Among the 26 different mixtures of extraction solvent and mixture ratios, ethanol extract mixture no. 1 (EM01) showed the highest antioxidant (α,α-Diphenyl-β-picrylhydrazyl, total phenolic contents) and anti-adipogenic (Oil-Red O staining) activities. EM01 inhibited lipid accumulation in 3T3-L1 adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The AST and ALT were reported to be transferred to plasma due to obesity operated oxidative damage to tissues [68]. Another study reported that AST and ALT were toxicity indicators and phytochemicals present in various plants reduced their plasma concentrations by improving liver and kidney functions [69]. The antioxidant role of phytochemicals is of pivotal nature which not only reduced obesity by improvising multiple site oriented metabolic processes, but also normalized the organ's function.…”
Section: Treatmentsmentioning
confidence: 99%
“…The AST and ALT were reported to be transferred to plasma due to obesity operated oxidative damage to tissues [68]. Another study reported that AST and ALT were toxicity indicators and phytochemicals present in various plants reduced their plasma concentrations by improving liver and kidney functions [69]. The antioxidant role of phytochemicals is of pivotal nature which not only reduced obesity by improvising multiple site oriented metabolic processes, but also normalized the organ's function.…”
Section: Treatmentsmentioning
confidence: 99%
“…This aquatic plant is consumed as food and has wide-ranging uses as a folk medicine [ 2 ]. Various parts of the sacred lotus including leaves, flowers, stamens, embryos, and rhizomes were previously reported to promote health benefits [ 3 , 4 , 5 , 6 , 7 ]. These medicinal applications are the results of high health-promoting compounds, such as phenolic acids and flavonoids [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…After that, the regular medium (10% FBS and 1% P/S) was refreshed every 2 days until the 8th day. 23…”
Section: Cell Culture and Differentiationmentioning
confidence: 99%
“…Cells were seeded at a density of 5 • 10 4 cells/well along with extracts (0-300 lg/mL) for 24 h. MTT reagent was added to the medium and incubated for 2 h. The medium was emptied, and the formazan salt was redissolved in dimethyl sulfoxide (DMSO; Sigma-Aldrich), gauged utilizing an ultraviolet (UV)-visible spectrometer (Multiskan FC; Thermo Fisher Scientific, Inc., Waltham, MA, USA) at 570 nm. 23 Oil Red O staining assay Cells were seeded at a density of 5 • 10 4 cells/well and induced to differentiate along with extracts (100 lg/mL). These mature adipocytes were washed with phosphate buffered saline (Lonza, Walkersville, MD, USA) and secured in 4% paraformaldehyde at room temperature for 1 h. After rinsing the secured cells with 60% isopropanol, they were stained with Oil Red O (Sigma-Aldrich) solution (0.35% Oil red O dye in 60% isopropanol) for 20 min and then washed with distilled water.…”
Section: Cell Viability Assaymentioning
confidence: 99%